Score:
"The old man, stooped and shaking" is an example of the _____.
attributive position
appositive position
predicate position

Question

Asked 1/28/2013 7:37:33 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

danasalters|Points 450|

rickjames|Points 884|

Expert answered|andrewpallarca|Points 18960|

Question

Asked 1/28/2013 7:37:33 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

what type of clause is this? The woman who just finished the marathon is tired.
noun

Question

Updated 11/20/2016 6:45:05 AM

1 Answer/Comment

The woman who just finished the marathon is tired.

Type of clause: adjective

Subordinate clause: who just finished the marathon.

Type of clause: adjective

Subordinate clause: who just finished the marathon.

Added 11/20/2016 6:45:03 AM

This answer has been confirmed as correct and helpful.

Is the verb of this sentence active or passive?
Were you given a second helping?
active
passive
**Weegy:** Were you given a second helping? The sentence is passive.
(More)

Question

Expert Answered

Updated 1/8/2017 11:29:24 AM

0 Answers/Comments

Since I stopped vacuuming, the house has become dusty.
type of clause: adverbnounadjective

Question

Updated 7/20/2014 12:02:45 PM

1 Answer/Comment

Since I stopped vacuuming, the house has become dusty.

Clause: Since I stopped vacuuming;

Type of clause: Adverb.

Clause: Since I stopped vacuuming;

Type of clause: Adverb.

Added 7/20/2014 12:02:45 PM

This answer has been confirmed as correct and helpful.

3(x + 5) - 2(x + 2) = 20
1
9
13 **Weegy:** x - 9 = -6x + 5;
x + 6x = 5 + 9;
7x = 14;
x = 14/7;
x = 2
**User:** Which of the following equations has no solution?
3x + 1 = 2x + 1
3x + 1 = 3x + 1
3x + 1 = 3x + 2 **Weegy:** 3x + 1 = 2x + 12
x = 11
**User:** 3x - 5x + 8x + x = 42
6
7
8 **Weegy:** x=5 is the answer. **User:** What is the percent of decrease on an item that went from $25 to $20?
20%
25%
80%
(More)

Question

Updated 5/29/2014 9:39:19 AM

4 Answers/Comments

3(x + 5) - 2(x + 2) = 20

3x + 15 - 2x - 4 = 20

x + 11 = 20

x = 20 - 11 = 9

3x + 15 - 2x - 4 = 20

x + 11 = 20

x = 20 - 11 = 9

Added 5/29/2014 9:36:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:58:33 AM]

3x + 1 = 3x + 2 has no solution.

3x + 1 = 3x + 2

3x - 3x = 2 - 1

0 = 1 which is a false statement, therefore, 3x + 1 = 3x + 2 has no solution.

3x + 1 = 3x + 2

3x - 3x = 2 - 1

0 = 1 which is a false statement, therefore, 3x + 1 = 3x + 2 has no solution.

Added 5/29/2014 9:37:32 AM

This answer has been confirmed as correct and helpful.

3x - 5x + 8x + x = 42

-2x + 8x + x = 42

6x + x = 42

7x = 42

x = 42/7 = 6

-2x + 8x + x = 42

6x + x = 42

7x = 42

x = 42/7 = 6

Added 5/29/2014 9:38:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:58:55 AM]

An adverb clause is introduced by a _____.
relative pronoun
subordinating conjunction
conjunctive adverb
**Weegy:** An adverb clause is introduced by a subordinating conjunction. (More)

Question

Updated 5/7/2014 9:02:30 AM

0 Answers/Comments

33,978,871

questions answered

There are no comments.